In-Situ Radiometric Study Along the Kaligandaki River: Focus on the Deepest Gorge - Khatri, Bal V.; Khanal, Raju (Journal of Nepal Physical Society, 2025)
An in-situ radiometric survey was conducted along the Kaligandaki River in Nepal, a geologically significant region that features the world’s deepest gorge and the presence of Shaligram fossilized ammonites, which hold both cultural and scientific importance. The Kaligandaki River, one of the major rivers of Nepal, originates from Damodarkund near Lomanthang, where large uranium deposits have been confirmed by the Department of Mines and Geology, Nepal. The Shaligram fossil is found exclusively in this region. For the study, a portable gamma-ray spectrometer (PGIS-2) equipped with a NaI(Tl) detector was used. Radiological hazard parameters associated with naturally occurring radionuclides were determined, including radium equivalent activity (Raeq ), absorbed gamma dose rate in air (ADR), annual effective dose rate (AEDR), external hazard index (Hex ), and internal hazard index (Hin ). Mean values of all three radionuclides exceeded the worldwide average values reported by UNSCEAR. Radiological parameters were found to be: Raeq = 96.02–421.04 Bq kg−1 (mean: 219.89 ± 72.89 Bq kg−1 ), Hin = 0.46–1.47 (mean: 0.81 ± 0.23), and Hex = 0.26–1.13 (mean: 0.59 ± 0.20), all within internationally accepted safety limits. This study highlights the necessity for periodic monitoring to ensure environmental and public safety in regions with elevated levels of naturally occurring radioactive materials.